Respuesta :

Answer:

{c = 25/4

{t = 6

{x = 1

Step-by-step explanation:

Solve the following system:

{2 (x - 6) + 5 = -5 | (equation 1)

{75 = 3 (3 t - 2) + 27 | (equation 2)

{x - 2/3 (6 c - 9) = -18 | (equation 3)

Express the system in standard form:

{0 c+0 t+2 x = 2 | (equation 1)

{0 c - 9 t+0 x = -54 | (equation 2)

{-(4 c) + 0 t+x = -24 | (equation 3)

Swap equation 1 with equation 3:

{-(4 c) + 0 t+x = -24 | (equation 1)

{0 c - 9 t+0 x = -54 | (equation 2)

0 c+0 t+2 x = 2 | (equation 3)

Divide equation 2 by -9:

{-(4 c) + 0 t+x = -24 | (equation 1)

{0 c+t+0 x = 6 | (equation 2)

{0 c+0 t+2 x = 2 | (equation 3)

Divide equation 3 by 2:

{-(4 c) + 0 t+x = -24 | (equation 1)

{0 c+t+0 x = 6 | (equation 2)

{0 c+0 t+x = 1 | (equation 3)

Subtract equation 3 from equation 1:

{-(4 c)+0 t+0 x = -25 | (equation 1)

{0 c+t+0 x = 6 | (equation 2)

{0 c+0 t+x = 1 | (equation 3)

Divide equation 1 by -4:

{c+0 t+0 x = 25/4 | (equation 1)

{0 c+t+0 x = 6 | (equation 2)

{0 c+0 t+x = 1 | (equation 3)

Collect results:

Answer: {c = 25/4

{t = 6

{x = 1